Study of the Impact of Quality of Patient Care on Discharge against Medical Advice Patients in a Tertiary Care hospital (Medico Legal Update, 2019)
A cross sectional study was conducted with a sample size of 200.Among the 200 cases of DAMA, 7.5% of cases were in the age range of 15–25 years, 11% were in the age range of 26–30 years, 19% were in the age range of 36–45 years,16.5% were in the age range of 46–55 years, 20% were in the age range of 56-65 years.26% were above the age of 65 years.35.5% of patients who took discharge against medical advice were illiterate (n = 200), followed by 28.5% with secondary education. The least number was distributed among pre-degree and graduation (5%, 14%). The peak DAMA rate was seen among dependent participants(43.5%),followed by the self-employed (36%) and private employees(15%).The least was noted among government employees(5.5%). 68% of the cases were diagnosed with acute illness and 32% were diagnosed with chronic illness. DAMA cases were considered from 11 units of in-patient service such as Medicine, Gastrology, Neuro Surgery,Neurology,Pulmonary Medicine, Obstetrics and Gynaecology, Orthopaedic Surgery,Oncology and Cardiology. The reasons for DAMA can be considered under two categories: patient related factors and hospital related factors. Patient related factors include the following: Wanting to go to another hospital (77.5%), financial burden (53%), no improvement in condition (45%),distance from hospital (43.5%),unsatisfied with treatment (43.5%),worsening of symptoms (18.5%),family issues (9.5%),re–admission (7.5%), influenced by other patients (1%) and language barrier (0.5%). Medical conditions included addiction to alcohol (2%) and decision to go for alternative treatment (2%). The hospital related factors were: Expensive hospital stay (60%), ineffective care (28.5%), inefficient staff (27%), unnecessary diagnostic procedures (25.5%), long waiting time (18%),neglected by hospital staff (16%), uncomfortable hospital stay (11.5%), crowded hospital (4%), inadequate facilities (3.5%), improper communication by staff and strict hospital policies(3%). The third objective was to assess the impact of the quality of patient care on discharge against medical advice patients in a tertiary care hospital. The study result shows that Quality related issues do have a significant impact on DAMA. The quality related issues consist of the following sub areas: Wanted to go to other hospital (77.5%), no improvement in patient condition (45%), unsatisfied with treatment (44.5%), inefficient staff (27%),ineffective care (20.5%),worsening of symptoms (18.5%), neglected by hospital staff (16%) and uncomfortable hospital stay (11.5%).